Cognitive Function May be a Predictor of Retinopathy Progression in Patients with Type 2 Diabetes. Issue 3 (May 2017) - Trento, Marina; Charrier, Lorena; Salassa, Martina; Merlo, Stefano; Passera, Pietro; Baltatescu, Anatolie; Cavallo, Franco; Porta, Massimo
Purpose: Microvascular and macrovascular complications of diabetes, such as retinopathy and nephropathy, progress over time and may be associated with cognitive decline. In this article, we aim to gain further insight into the association between cognitive function and retinopathy in type 2 diabetes. Methods and Results: In this observational 8-year prospective study of 498 outpatients, demographic and clinical variables were monitored, along with retinopathy, depression, anxiety, and cognitive function. Baseline fundus photographs were available in 477 patients, 240 with no retinopathy, 110 with mild retinopathy, and 127 with moderate/more severe retinopathy. Of the first 2 groups, 279 patients were reevaluated after 8 years, of whom 181 still had no/mild retinopathy and 98 had progressed to more severe stages. On multivariate analysis, retinopathy progression was associated with being insulin-treated (p = 0.036), and worse cognitive function (p = 0.025) at baseline. Conclusions: Cognitive function may be an independent predictor of retinopathy progression.